Whole Exome Sequencing Study in Isolated South-Eastern Moravia (Czechia) Population Indicates Heterogenous Genetic Background for Parkinsonism Development - Kolarikova, Kristyna; Vodicka, Radek; Vrtel, Radek; Stellmachova, Julia; Prochazka, Martin; Mensikova, Katerina; Kanovsky, Petr (Frontiers in Neuroscience, 2022)
Parkinsonism belongs to the most common neurodegenerative disease. Genetic predisposition could be one of the significant risk factor for disease development. It has been described higher prevalence of parkinsonism in large pedigree from southeastern Moravia region. The study aims were to select accessible subfamily trios from the pedigree suitable for segregation genetic analyses to perform whole exome sequencing in trio individuals and further to evaluate genetic variants in the each trio. We used IonTorrent platform for whole exome sequencing for five subfamily trios (1-5). Each trio included two affected and one healthy person (as control). Found variants were filtered with respect to MAF˂1% (minor allele frequency), variants effect (based on prediction tools) and disease filter (Parkinsonism responsible genes). Finally, the variants from each trio were assessed with respect to the presence in the patients. There were found no one founder mutation in the subfamilies from the pedigree. Trio 1 shares two variants with trio 2:MC1R:c.322G>A (p.A108T) and MTCL1:c.1445C>T (p.A482V), Trio 3 shares two variants with trio 5: DNAJC6:c.1817A>C (p.H606P) and HIVEP3:c.3856C>A (p.R1286W). In trios 4 and 5, there were found two variants in gene CSMD1:c.3335A>G (p.E1112G) and c.4071C>G (p.I1357M) respectively. As the most potentially damaging, we evaluated the nonshared variant SLC18A2:c.583G>A (p.G195S). The variant could affect dopamine transport in dopaminergic neurons. The study of the parkinsonism genetic background in isolated Moravian population suggested that there could be significant accumulation of many risk genetic factors. For verification of the variants influence, it would be appropriate to perform a more extensive population study and suitable functional analysis.